2013
DOI: 10.1111/den.12138
|View full text |Cite
|
Sign up to set email alerts
|

Primary esophageal mucosa‐associated lymphoid tissue lymphoma treated by endoscopic submucosal dissection

Abstract: Primary esophageal mucosa-associated lymphoid tissue (MALT) lymphoma is rare. There have been few reports about early primary esophageal MALT lymphoma being treated endoscopically. The clinical profile of primary esophageal MALT lymphoma is currently unclear, so it is important to accumulate more information about early esophageal MALT lymphoma. To achieve early detection of esophageal MALT lymphoma, we need more accurate knowledge and information about the macroscopic and morphological features of this tumor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The present case showed both of these endoscopic findings, and we additionally observed the presence of abnormal blood vessels similar to a tree-like appearance, which is a typical characteristic of gastric lesions in MALT lymphoma (39, 40). This characteristic was recently reported in an esophageal lesion by Kudo et al (25). These radiological and endoscopic characteristics may be helpful in detecting esophageal MALT lymphoma lesions, and should prompt endoscopists to perform a biopsy to obtain specimens for histological examination.…”
Section: Discussionsupporting
confidence: 80%
“…The present case showed both of these endoscopic findings, and we additionally observed the presence of abnormal blood vessels similar to a tree-like appearance, which is a typical characteristic of gastric lesions in MALT lymphoma (39, 40). This characteristic was recently reported in an esophageal lesion by Kudo et al (25). These radiological and endoscopic characteristics may be helpful in detecting esophageal MALT lymphoma lesions, and should prompt endoscopists to perform a biopsy to obtain specimens for histological examination.…”
Section: Discussionsupporting
confidence: 80%
“…Lymphoma was localized in the esophagus in 15 cases, and the remaining patient had involvement of the stomach ( 4 ). In patients with localized disease, esophageal MALT lymphoma can be curatively removed by surgical resection ( 9 , 19 , 25 ) or endoscopic resection ( 6 , 14 , 20 ), as shown in our present patient. Previous studies have demonstrated that endoscopic resection alone resulted in complete remission for 1 year, 22 months, and 2 years after resection.…”
Section: Discussionsupporting
confidence: 62%
“…Some had non-specific symptoms and the esophageal lesion was detected during a routine medical check-up. [15] Several approaches, such as endoscopic examination, endosonography of the upper gastrointestinal tract, and chest CT scan, were used to examine the esophageal lesion in clinical practice. However, it was difficultly to confirm the diagnosis of esophageal MALT lymphoma through these methods.…”
Section: Discussionmentioning
confidence: 99%